Legal Analysis of Communal Rights of Ammatoa Kajang Customary Law Community On Customary Forest In Bulukumba District - Ade Putra Frima Sumbara (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to find out the implementation of the communal rights of the Ammato Kajang customary law community in the customary forest in the Bulukumba district and to find out to what extent the communal rights of the Ammatoa Kajang customary law community are protected by law. The research method used is Normative Law research. The results showed that the implementation of the communal rights of the Ammatoa Kajang indigenous people was carried out on the authority of the Ammatoa based on "pairs of rikajang" which is a source of law to regulate all aspects of the life of the Ammatoa Kajang indigenous people who are related to God (Turiek Arakna). And the customary law of the ammatoa Kajang relies heavily on "Pasang Rikajang", this deliberation effectively resolves the problem, and the results of the deliberation become the source of the birth of the Bulukumba Regency Regional Regulation Number 9 of 2015 Concerning the Inauguration, Recognition of Rights, and Protection of the Rights of Indigenous Peoples